Conservation of Male Sterility 2 function during spore and pollen wall development supports an evolutionarily early recruitment of a core component in the sporopollenin biosynthetic pathway. Issue 1 (7th September 2014) - Wallace, Simon; Chater, Caspar C.; Kamisugi, Yasuko; Cuming, Andrew C.; Wellman, Charles H.; Beerling, David J.; Fleming, Andrew J.
Summary: The early evolution of plants required the acquisition of a number of key adaptations to overcome physiological difficulties associated with survival on land. One of these was a tough sporopollenin wall that enclosed reproductive propagules and provided protection from desiccation and UV‐B radiation. All land plants possess such walled spores (or their derived homologue, pollen). We took a reverse genetics approach, consisting of knock‐out and complementation experiments to test the functional conservation of the sporopollenin‐associated gene MALE STERILTY 2 (which is essential for pollen wall development in Arabidopsis thaliana ) in the bryophyte Physcomitrella patens . Knock‐outs of a putative moss homologue of the A .  thaliana MS2 gene, which is highly expressed in the moss sporophyte, led to spores with highly defective walls comparable to that observed in the A. thaliana ms2 mutant, and extremely compromised germination. Conversely, the moss MS2 gene could not rescue the A. thaliana ms2 phenotype. The results presented here suggest that a core component of the biochemical and developmental pathway required for angiosperm pollen wall development was recruited early in land plant evolution but the continued increase in pollen wall complexity observed in angiosperms has been accompanied by divergence in MS2 gene function.